Toxic Relationship in Emerging Adulthood - Zein Permana; Koentjoro Koentjoro; Muhammad Najib Azca (Jurnal Wanita dan Keluarga, 2023)
This study aims to explore the primary concerns of emerging adulthood in Bandung, Indonesia, and the psychological dynamics that occur in their lives during this stage. Using a three-phase approach, a survey was conducted among 1034 participants (mean age = 20.4) to identify their current concerns. A grounded approach was employed in the second phase to determine the recurring themes of concern. The findings indicate that the primary concern of emerging adults is related to potentially toxic romantic relationships. To gain a deeper understanding of the psychological dynamics associated with these relationships, in-depth interviews were conducted with 11 emerging adults who had experienced toxic relationships. The results revealed five critical areas within toxic relationships, including: 1) reasons for initiating the relationship; 2) the "something is wrong" phase; 3) adverse outcomes of the relationship; 4) strategies for ending the relationship; and 5) expectations that emerge and develop as the relationship ends. In conclusion, this study provides insights into the primary concerns of emerging adulthood regarding toxic romantic relationships. The findings have important implications for the development of interventions and more effective approaches to help emerging adults manage their romantic relationships.